Relation of TGF-β1 gene with the prognosis of patients with Covid-19 (Research, Society and Development, 2022)
This study aimed to investigate the role of the TGF-β1 gene in SARS-CoV-2 infection. A total of 178 individuals diagnosed with Covid-19 participated and, they were divided in two groups related to the outcome (discharge or death). Genotyping of rs1800468 and rs1800469 polymorphisms of TGF-β1 gene was performed in 178 samples, using the allelic discrimination technique and, gene expression analysis was performed in 93 samples by Real Time PCR. There was no association between the genotypic frequencies of TGF-β1 gene polymorphisms analyzed with the prognosis of patients with Covid-19. There was no significant difference between gene expression and the clinical data evaluated. A statistically significant difference was observed in the expression of the TGF-β1 gene between the CT and TT genotypes of the rs1800469 polymorphism, with lower gene expression in the presence of the TT genotype. Regarding the rs1800468 polymorphism, no statistically significant difference was observed in the expression of the TGF-β1 gene in relation to the analyzed genotypes. The present study concluded that the rs1800468 and rs1800469 polymorphisms of the TGF-β1 gene are not associated with the prognosis of patients with Covid-19 and which the TT genotype of the rs1800469 polymorphism reduces the expression of TGF-β1.